What does it mean to be Prai? Competing definitions of identity - F. Jason Diller; Douglas M. Fraiser; Kari Jordan Diller (Journal of Integrative and Innovative Humanities, 2023)
This article examines contrasting views of ethnic identity for the Prai – an Austroasiatic ethnic minority group living in Nan Province, Thailand. Collins and Blot’s (2003) theory of “given” and “formed” identities is used to contrast the Thai written presentation of the Prai (given) with the Prai oral presentation of their own ethnic identity (formed). Thai written descriptions of Prai ethnic identity are presented in contrast to Prai descriptions of their own identity. Three traditional Prai folk stories are used to show how they depict their own cultural values. Research methods include document collection of written texts and the translation of previously unpublished oral folk stories. An analysis of findings reveals that the Prai have been negatively positioned as people without Buddhist merit, slow to change, or resistant to progress. In contrast, the Prai are aware of this positioning and flip the narrative to highlight their spiritual merit, communal strength, and exceptional use of forest resources among other intrinsic Prai cultural values. Such a contrast of identity narratives for the Prai has never been made in academic research and looking to the future necessitates exploring these contradictions about what it means to be “Prai.”